Evaluation of gelatin methacryloyl hydrogels containing decellularized bovine bone matrix applied for dentin regeneration - Silva, Isabela Sanches Pompeo da (2023)
The search for minimally invasive regenerative strategies that induce reparative dentin formation by stimulating resident pulp cells has been studied in the field of Regenerative Dentistry. In this study, the incorporation of bovine bone matrices to gelatin methacrylate (GelMA) was proposed, intending to develop a photopolymerizable biomimetic hydrogel for dentin engineering. Initially, the manufacturing parameters of GelMA were selected in dose-response tests, based on the study of the degradability and viability of pulp cells, with the hydrogels being manufactured with 15% of GelMA and 0.075% of photoinitiator (LAP; Lithium Acylphosphinate), and photoactivated for 30s. Next, microparticles were produced from bovine bone tissue submitted to the decellularization processes (BMdc), where the cellular content was removed, and deproteinization (BMdp), where all organic content was eliminated. From an initial screening, the concentration of 1% (w/v) of bone matrix was selected, as it promotes better cell interaction. Thus, the following groups were established: GelMA-BMdc GelMA incorporated with 1% BMdc; GelMA-BMdp - GelMA incorporated with 1% BMdp; GelMA-nHA - GelMA incorporated with 1% nano-hydroxyapatite; GelMA hydrogel without incorporation (negative control). The hydrogels were prepared, injected, and light-cured in 96-compartment plates, with human pulp cells seeded in their structure. Biological assays of cell viability and proliferation (Live/Dead and Alamar Blue), and odontoblastic differentiation (ALP activity and Alizarin Red) were performed. The hydrogels were evaluated by scanning electron microscopy (SEM), to observe the architecture and evaluate the porosity (ImageJ), and by Fourier transform infrared spectroscopy (FTIR), to evaluate the chemical structure. In addition, a degradability test with enzymatic challenge was performed. Data were analyzed using ANOVA and Tukey tests (=5%). Viable and proliferative cells were observed in all groups without significant differences. The incorporation of bone matrices resulted in a significant increase in ALP activity and mineralized matrix deposition compared to GelMA, and the GelMA-BMdc group showed significantly higher values than all other experimental groups. The FTIR-ATR spectra confirmed the composition of bone matrices and their complexation to gelatin, as well as the chemical binding of BMdc to the structure of GelMA. Incorporating bone matrices did not change the pattern of GelMA degradability; however, BMdp and nHA altered the porosity pattern, generating smaller pore diameter values than pure GelMA. This effect was not observed for GelMA-BMdc. Thus, we conclude that the incorporation of bovine bone matrix submitted to decellularization to GelMA resulted in a stable and porous hydrogel with high bioactivity on human pulp cells, presenting itself as an alternative biomaterial that can be injected and photopolymerized in situ in pulp exposures for the regeneration of dentin.